Care for a patient with Mirizzi Syndrome (Salud, Arte y Cuidado, 2017)
Bile duct disease is one of the most common pathologies in the Surgery Department. Mirizzi Syndrome is one of the uncommon complications of these pathologies. It is more frequent in developing countries, reaching in Latin America between 4.7% and 5.7% of the cases. The present investigation aims to identify domains and affected classes to a patient with Mirizzi Syndrome. Case study in a 45-year-old female patient with a history of obstructive secondary jaundice to choledocholithiasis who had required placement of a plastic prosthesis using endoscopic retrograde cholangiopancreatography (ERCP) to ensure drainage of the biliary tract, due to the impossibility of extracting it through trawls with Fogarty's ball. Lithiasis in cystic duct that initially did not condition obstruction of the main biliary tract was also observed in a public health institution in the city of Barquisimeto, Lara State, Venezuela. Nursing care was administered through the nursing process. Nursing assessment was performed with the Nursing Diagnostics Taxonomy II. The domains and affected classes were described in the postoperative period; the nursing care plan was implemented with the diagnostic interrelationships, interventions and results. Results: The patient progressed unfavorably, dying after 60 days due to complications. Conclusions: At the end of the investigation of the case, it was observed the importance of carrying out the nursing care plan with the respective interrelations to provide quality care.
Keywords: mirizzi syndrome; nurse process; NANDA; NIC; NOC